Analysis of the Hydrological Properties of Wetlands: A case study of Pong Dam Lake, Himachal Pradesh - Maansi Malik and Prem Prakash (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Wetlands are critical ecosystems that provide essential ecological services, including water purification, flood regulation, and biodiversity support. This study focuses on analyzing the hydrological properties of Pong Dam Lake, a prominent wetland in Himachal Pradesh, India, using advanced remote sensing methods. The research aims to understand the dynamic hydrological processes governing the lake's seasonal and spatial variations, leveraging satellite-based tools like Landsat imagery, coupled with Geographic Information System (GIS) analytics. The study employs multi-temporal and multi-spectral datasets to assess key hydrological parameters such as surface water extent, water depth, and temporal inundation patterns. Spectral indices like the Normalized Difference Water Index (NDWI) and Modified Normalized Difference Water Index (MNDWI) are utilized to enhance waterbody delineation accuracy. Furthermore, Digital Elevation Models (DEMs) are integrated to evaluate the topographical influences on water distribution. The analysis reveals significant seasonal variations in water levels and inundation extents, driven by monsoonal patterns and dam operations.